The Influence of Financial Attitudes and Lifestyle On Financial Literacy (Case Study of Housewives in Lekong Village, West Alas District, Sumbawa Regency) - Salam, Abdul; Mulyati, Indah (Universitas Negeri Semarang, 2021)
This study aims to examine whether financial attitudes and lifestyle have an effect on financial literacy in housewives in Lekong Village, West Alas District, Sumbawa Regency. The study wanted to find the phenomenon of the role of women in improving the welfare of society which is quite large, while on the other hand, the level of financial literacy of women in Indonesia is lower than men. This study uses quantitative methods, the sampling technique uses probability sampling method simple random sampling. The sample in this study may be 100 respondents of housewives in Lekong Village, West Alas District, Sumbawa Regency, obtained by distributing questionnaires. Data analysis in this study using multiple linear regression using SPSS software. The results showed that the variables of financial attitudes and lifestyle had a positive and significant effect on financial literacy.